Sustainable production of tuberose (Polianthes tuberosa) through integrated nutrient management : a review (Current Horticulture, 2024)
Tuberose (Polianthes tuberose L.) is most important cut flower. The recent energy crisis and hike in prices of fertilizers, further necessitate the use of alternate sources, i.e. organic manures and biofertilizers. But no single source of plant nutrients either it is chemicals, organic manures or even biofertilizers could meet the entire need of the crop. Therefore, there is a need of integrated nutrient management (INM). This holistic approach has profound effect in improving flower quality and yield. The INM also provides an excellent opportunity to overcome all the imbalances besides sustaining soil health. The paper reviews all the literature on various aspects of tuberose cultivation from INM perspective for better understanding and future strategies for improved flower quality and yield of tuberose.
Keywords: Biofertilizers; Fertilizers; Integrated nutrient management; Manures